A 10-YEAR REVIEW OF OPEN-GLOBE TRAUMA IN ELDERLY PATIENTS AT AN URBAN HOSPITAL. Issue 1 (January 2015) - Sheng, Iris; Bauza, Alain; Langer, Paul; Zarbin, Marco; Bhagat, Neelakshi
Abstract : Background: To describe the demographics, characteristics, and outcomes of open-globe injuries (OGIs) in elderly patients. Methods: Retrospective chart review. Results: Ninety cases (26 men) were identified. The average age was 80 years (range, 65–96 years). The types of OGIs included rupture (83.3%) and penetrating (16.7%) injuries. The causes of trauma were falls (64.4%), accidents (20%), motor vehicle accidents (5.5%), and assault (3.33%). Types of lacerations included corneal (44.4%), corneoscleral (26.7%), and scleral (28.9%). Forty-six cases were OGIs because of dehiscence of previous ocular surgical wound. Ten eyes had concurrent orbital fractures. Approximately 81.1% of cases underwent primary OGI repair within 24 hours of injury, and all cases underwent primary OGI repair within 24 hours of admission. The average visual acuity at presentation was 20/4, 375 (SD, 0.64). Although 22 patients presented with no light perception, only 10 remained no light perception after OGI repair. Complications at presentation included uveal prolapse (70%), hemorrhagic choroidal detachment (37.8%), vitreous hemorrhage (51.1%), retinal detachment (20%), and afferent pupillary defect (42.2%). Three patients (3.33%) underwent primary pars plana vitrectomy for retinal detachment and vitreous hemorrhage. Three patients developed endophthalmitis. Overall, retinal attachment was achieved in all eyes that underwent primary pars plana vitrectomy. Primary enucleations were performed in 4 cases (4.44%) for nonsalvageable no light perception eyes. Conclusion: The visual prognosis of OGIs in the elderly population is poor; only 14.4% achieved 20/200 or better visual acuity. Precautionary measures should be taken to prevent OGIs in the elderly population. Abstract : A 10-year review of open-globe injuries in the elderly population who presented to an urban hospital. This article describes the demographics, characteristics, and outcomes of this specific population. This article hopes to increase awareness of the various causes of open-globe injuries in this high-risk population.